Integration of socio-ecological data to prioritize biodiversity hot-spots for Marine Protected Area (MPA) delineation in the coastal zone of Bangladesh - Sarker, Subrata; Hossain, Md. Shahadat; Das, Nabanita; Riya, Shashowti; Smriti, Sagorika; Mokarrom, Hossain; Rahman, Mohammad (Elsevier, 2024)
Marine Protected Areas (MPAs) are widely used tools for conserving coastal and marine biodiversity and ecosystem health. However, the goal of declaring and managing at least 10 % of coastal and marine waters as MPAs has not been achieved in Bangladesh and many other countries. This study aimed at prioritizing the potential areas for MPA delineation in the south-west coastal zone of Bangladesh. The study also examined the socio-economic status, environmental and ecological characteristics of the study areas. Data on socio-economic, environmental, ecological, and management variables were collected through intensive field surveys from August 2023 to December 2023. The data were integrated using a multi-criteria analytical technique. Fishing was identified as the primary occupation for all fishermen surveyed, with secondary occupations including fish selling, marketing, and drying activities. The fishing areas for fishermen from the three survey sites were mainly concentrated in the offshore area. All three areas were identified as biodiversity hotspots, with Kuakata coast showing the highest species diversity, followed by Salimpur and Sandwip coasts. The study revealed that the Kuakata coast has the highest conservation importance, especially for IUCN red-listed species, juvenile fisheries species, and megafauna species. Salimpur coast is important for the conservation of saltmarshes, mangroves, and their dependent communities, while Sandwip is crucial for juvenile fish species conservation. Based on socio-ecological criteria, Kuakata was recommended as the most potential site for MPA delineation, followed by Salimpur and Sandwip. Implementing these recommendations can improve the management and execution of existing MPAs by focusing conservation efforts on areas with the highest biodiversity and ecological importance, ensuring better protection for vulnerable species, and enhancing the sustainability of local fishing communities. This, in turn, will ultimately enhance biodiversity conservation and ecosystem health in the southwest coastal area of Bangladesh.